The Influence of Social Media Marketing and Brand Image on the Shopee Application on UGREEN Product Purchase Decisions - Zata Aman, Yosanda; Setyawati, Dyah; Widiawati, Diah (Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the influence of social media marketing and brand image on the purchase decision of UGREEN products on the Shopee e-commerce platform. The research method uses a quantitative approach with data collection through online questionnaires distributed to 97 students of the Faculty of Economics and Business, Universitas Merdeka Malang. The analysis results show that social media marketing and brand image have a significant influence on purchase decisions. Social media marketing affects purchase decisions through engaging content, audience interaction, and effective promotions, while brand image builds consumer trust and loyalty through positive perceptions of the brand. This study provides recommendations for companies to optimize digital marketing strategies and brand image management to increase product sales on e-commerce platforms.